Dynamic switching-induced back-carrier-injection in a-InGaZnO thin film transistors. (22nd October 2020) - Tai, Mao-Chou; Tsao, Yu-Ching; Wang, Yu-Xuan; Lin, Chih-Chih; Tsai, Yu-Lin; Tu, Hong-Yi; Huang, Bo-Shen; Chang, Ting-Chang
Abstract: In this work, degradation due to carrier injection at the etch-stop layer was observed under dynamic switching. A significant threshold voltage shift is observed in alternating current stress but is absent in direct current stress. A model which transitions from the accumulation to depletion phases indicates electron-trapping at the etch-stop layer since the transition time is insufficient for carriers to drift back to the source/drain electrodes. Results are discussed through both horizontal and lateral band diagrams to confirm back channel injections. Also, comparing transfer curves with capacitance-voltage curves at the same threshold voltage in different structure devices provides direct evidence of electron-trapping regions. Finally, COMSOL simulation is performed to confirm the difference in electron-trapping between back channel and corner regions, a difference which leads to an abnormal hump during capacitance-voltage measurements.